The Influence of Financial Literacy, Income and Self-Control on the Financial Behaviour of MSMEs in Pemalang Regency - Suci Indah Sari; Ika Yustina Rahmawati; Nawalin Nazah; Restu Frida Utami (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyse the influence of financial literacy, income, and self-control on the financial behaviour of MSME actors in Pemalang Regency. The research employed a quantitative method with an explanatory approach, and data were collected through questionnaires from 100 MSME respondents selected using purposive sampling techniques. Data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results show that financial literacy, income, and self-control have a positive and significant effect on financial behaviour. These findings indicate that good financial understanding, adequate income, and strong self-control play an important role in shaping rational and sustainable financial behaviour. The R-square value of 0.663 shows that the three variables explain 66.3% of the variation in MSME financial behaviour. Therefore, improving financial literacy and strengthening self-control should be prioritised in efforts to develop sound financial behaviour among MSME actors in Pemalang Regency.